Quantum work statistics and resource theories: Bridging the gap through Rényi divergences - Guarnieri, Giacomo; Ng, N. H. Y.; Modi, Kavan; Eisert, Jens; Paternostro, Mauro; Goold, John (Physical Review E, 2019)
The work performed on or extracted from a nonautonomous quantum system described by means of a two-point projective-measurement approach is a stochastic variable. We show that the cumulant generating function of work can be recast in the form of quantum Rényi-α divergences, and by exploiting the convexity of this cumulant generating function, derive a single-parameter family of bounds for the first moment of work. Higher order moments of work can also be obtained from this result. In this way, we establish a link between quantum work statistics in stochastic approaches and resource theories for quantum thermodynamics, a theory in which Rényi-α divergences take a central role. To explore this connection further, we consider an extended framework involving a control switch and an auxiliary battery, which is instrumental to reconstructing the work statistics of the system. We compare and discuss our bounds on the work distribution to findings on deterministic work studied in resource-theoretic settings.
CRIS-Team Scopus Importer:2023-04-20